Response strategies of fine root morphology of Cupressus funebris to the different soil environment - Wen, Xiaochen; Wang, Xiao; Ye, Mengting; Liu, Hai; He, Wenchun; Wang, Yu; Li, Tianyi; Zhao, Kuangji; Hou, Guirong; Chen, Gang; Li, Xianwei; Fan, Chuan (Frontiers in Plant Science, 2022)
Understanding fine root morphology is crucial to uncover water and nutrient acquisition and transposition of fine roots. However, there is still a lack of knowledge regarding how the soil environment affects the fine root morphology of various root orders in the stable forest ecosystem. Therefore, this experiment assessed the response strategies of fine root morphology (first- to fifth -order fine roots) in four different soil environments. The results showed that fine root morphology was related to soil environment, and there were significant differences in specific root length (SRL), specific surface area (SRA), diameter (D), and root tissue density (RTD) of first- and second -order fine roots. Soil total nitrogen (TN), alkaline nitrogen (AN) and available phosphorus (AP) were positively correlated with SRL and SRA and negatively correlated with D and RTD. Soil moisture (SW) was positively correlated with the D and RTD of first- and second-order fine roots and negatively correlated with the SRL and SRA. Soil temperature (ST), organic carbon (OC), soil bulk density (SBD) and soil porosity (SP) were not significantly correlated with the D, SRL, SRA, and RTD of the first- and second -order fine roots. AN was positively correlated with SRL and SRA and negatively correlated with both D and RTD in the first- and second -order fine roots, and the correlation coefficient was very significant. Therefore, we finally concluded that soil AN was the most critical factor affecting root D, SRL, SRA and RTD of fine roots, and mainly affected the morphology of first- and second -order fine roots. In conclusion, our research provides support for understanding the relationship between fine root morphology and soil environment, and indicates that soil nutrient gradient forms good root morphology at intraspecific scale.